Diagnosis of Prostate Cancer with a Neurotensin-Bombesin Radioligand Combination-First Preclinical Results - Maria Bibika; Panagiotis Kanellopoulos; Maritina Rouchota; George Loudos; Berthold A. Nock; Eric P. Krenning; Theodosia Maina (MDPI AG, 2024)
Background: The concept of radiotheranostics relies on the overexpression of a biomolecular target on malignant cells to direct diagnostic/therapeutic radionuclide-carriers specifically to cancer lesions. The concomitant expression of more than one target in pathological lesions may be elegantly exploited to improve diagnostic sensitivity and therapeutic efficacy. Toward this goal, we explored a first example of a combined application of [99mTc]Tc-DT11 (DT11, N4-Lys(MPBA-PEG4)-Arg-Arg-Pro-Tyr-Ile-Leu-OH; NTS1R-specific) and [99mTc]Tc-DB7(DB7, N4-PEG2-DPhe-Gln-Trp-Ala-Val-Gly-His-Leu-NHEt; GRPR-specific) in prostate cancer models. Methods: Accordingly, the behavior of [99mTc]Tc-DT11 was compared with that of the [99mTc]Tc-DT11+[99mTc]Tc-DB7 mixture in prostate adenocarcinoma PC-3 cells and xenografts in mice. The impact of stabilizing both radiotracers by Entresto®, as a source of the potent neprilysin inhibitor sacubitrilat, was also investigated. Results: The PC-3 cell binding of the [99mTc]Tc-DT11+[99mTc]Tc-DB7 mixture surpassed that of [99mTc]Tc-DT11. Likewise, the PC-3 tumor uptake of the [99mTc]Tc-DT11+[99mTc]Tc-DB7 mixture at 4 h post-injection was superior (7.70 ± 0.89%IA/g) compared with [99mTc]Tc-DT11 (4.23 ± 0.58%IA/g; p < 0.0001). Treatment with Entresto® led to further enhancement of the tumor uptake (to 11.57 ± 1.92%IA/g; p < 0.0001). Conclusions: In conclusion, this first preclinical study on prostate cancer models revealed clear advantages of dual NTS1R/GRPR targeting, justifying further assessment of this promising concept in other cancer models.